2003
DOI: 10.1021/jf0210472
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Enzyme-Linked Immunosorbent Assay for the Insecticide Thiamethoxam

Abstract: An enzyme-linked immunosorbent assay (ELISA) was developed for the neonicotinoid insecticide thiamethoxam, 3-(2-chlorothiazol-5-ylmethyl)-5-methyl-4-nitroimino-1,3,5-oxadiazinane. Three antisera were raised from rabbits immunized with the hapten-KLH conjugate. On the basis of the computational analysis of hapten candidates, the hapten with a spacer arm on the thiazolyl ring of thiamethoxam was synthesized to elicit thiamethoxam-specific antisera. The hapten was 3-[2-(2-carboxyethylthio)-5-ylmethyl]-5-methyl-4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 32 publications
0
36
0
Order By: Relevance
“…Since thiamethoxam is widely used as plant protecting agent in many countries, its determination at trace levels is an acute analytical problem. The methods that have been applied for its assay in agricultural and environmental samples involved high-performance liquid chromatography (HPLC) with diode-array [22,23] and mass-spectrometric [24,25] detection, as well as enzyme-linked immunosorbent assay [26]. The reduction mechanism of thiamethoxam at a dropping mercury electrode (DME) and its voltammetric determination either in model systems or thiamethoxam-treated samples, using glassy carbon (GCE) and static mercury drop electrodes (SMDE), were reported in our previous works [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Since thiamethoxam is widely used as plant protecting agent in many countries, its determination at trace levels is an acute analytical problem. The methods that have been applied for its assay in agricultural and environmental samples involved high-performance liquid chromatography (HPLC) with diode-array [22,23] and mass-spectrometric [24,25] detection, as well as enzyme-linked immunosorbent assay [26]. The reduction mechanism of thiamethoxam at a dropping mercury electrode (DME) and its voltammetric determination either in model systems or thiamethoxam-treated samples, using glassy carbon (GCE) and static mercury drop electrodes (SMDE), were reported in our previous works [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Chemical effects on assay performance were evaluated, which included: ionic strength, pH and organic solvent. As well known 32,35,36 those factors can affect assay to different degrees. We studied those factors for the application of immunoassay to the analysis of DES residue, and the good recovery of DES in water samples showed that the assay can be used for the determination of DES residues in water, but further work is needed to validate this assay with other matrices.…”
Section: Resultsmentioning
confidence: 99%
“…Watanabe et al (2001) and Kim et al (2004) developed monoclonal antibody (MoAb) specific to imidacloprid, and constructed ELISA that is 5-fold to 20-fold more sensitive than that obtained using PoAb. In addition to imidacloprid, ELISA using MoAb specific to acetamiprid (Watanabe et al, 2001) and thiamethoxam (Kim et al, 2003(Kim et al, , 2006 were also developed. As described above, ELISA uses highly specific antigen-antibody reaction.…”
Section: Elisa Analysis For Neonicotinoid Insecticides As a Rapid Andmentioning
confidence: 99%